The effectiveness of leadership: meta-analysis of trial, cross-sectional, and before after studies. (30th September 2020) - Restivo, V; Gaeta, M; Odone, A; Trucchi, C; Battaglini, A; Carli, A; Capraro, M; Minutolo, G; Casuccio, A; Favaretti, C
Abstract: Background: The clinical and surgical procedures are often based on scientifical evidence but 30-40% of patients do not receive treatment according to evidence based medicine. The main aim of this review and meta-analysis is to assess the effectiveness of leadership in healthcare setting. Methods: It was conducted a literature research on MEDLINE, Pubmed and Scopus with publication year between 2015 and 2019. The inclusion criteria were studies involving healthcare workers that evaluated effectiveness of opinion leaders in improving behaviour of healthcare workers, according to clinical or patient related outcomes. The quality of studies were assesed with the NHLBI for before after studies and the NOS for other study designs. The effect of leadership was assessed as risk difference for all studies with the exception of cross sectional studies. For the last it was evaluated correlation between leadership level and outcome measurment. Results: A total of 3, 155 articles were screened and 284 were fully assessed including 22 of them in the final database: 1 randomized trial, 9 cross sectional and 12 before after studies. For the cross-sectional studies there was a correlation of 0.22 (95% CI 0.15-0.28) between leadership level and outcome measurment. In the metaregression analysis the only factor that increased the correlation was private setting (meta regression coefficent =0.52, p = 0.022). The pooled efficacy was 24% (95% CI 10%-17%) for before after studies. Furthermore, a higher effectiveness was revealed in studies conducted on multi professional (24%) than single professional (9%) healthcare workers. Conclusions: According to results, the guidelines adherence and task performance increased in a setting with leadership implementation. The leadership effectiveness appears comparable to other strategies as audit and feedback used to implement evidence-based practice in worldwide healthcare. Key messages: The translation of evidence into clinical practice is often difficult but this study suggests that leaderhip can had higher effectiveness in multiprofessional healthcare workers and private setting. The effectiveness of leadership in this review suggests that it can be of help in order to make aware healthcare professionals about effectiveness of comply with evidence-based practice.